An Elementary Proof of Weisman’s Congruence When p=2 - Neuberger, Nick; Yildiz, Bahattin (The PUMP Journal of Undergraduate Research, 2020)
We give an elementary approach to proving divisibility results for a class of binomial sums that are similar to Fleck's congruence. We use tools that are accessible to undergraduate students and in proving the divisibility results, we obtain additional interesting properties that we highlight in several parts of the paper.